Efficiency comparison of capacitive wireless power transfer for different materials - F. K. A. Rahman; Shakir Saat; Y. Yusop; S. H. Husin; M. H. Jamaluddin (Institute of Advanced Engineering and Science, 2020)
This paper describes the application of several types of materials to act as capacitive plates in a Capacitive Power Transfer (CPT) system. In general, the efficiency of CPT system is greatly influenced by the coupling capacitance which is varied by distances and permittivity values. Thus this paper intended to compare the performance of CPT system in terms of the output efficiency for several types of capacitive plates. To be specific, copper plate, zinc, and aluminium are used in this work to act as coupling plates to the CPT system. The CPT system in this work applied class E inverter as it has lowest switching losses among its competitors, i.e. class D and class F. The work is validated through experimental setup of CPT system in which copper material provides the best efficiency of the system.